(3OaY GdeVGQ GdcdjI ddCHOGf GdEfSGfjIs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg Mb MeOg hHYO aEf GdTjN GdLdjd CHG GdMSf CMeO Hf eMeO GdSgdi , YQa HYdh GdgeI CeQfi ajeG CeQ ef GdChGeQ GdMcejI Cf GYed cJGHkG ai OaY GdeVGQ GdcdjI ddCHOGf GdEfSGfjI s
(3BNQgG (B:s
(3hGeG efY GdESgGd Gh JOHjQ ef de jSgd agh ehLhO aj GdcJH , hdjcf gPG cGajG ai ZQVfG hGdMeO ddg QH GdYGdejf s
(3fSNI QGHYIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B95 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WH e (B19) s
Keywords: (3GdWHs